2021
DOI: 10.36615/sotls.v5i2.192
|View full text |Cite
|
Sign up to set email alerts
|

“You become academic royalty once you’ve published”: A social practice exploration of identity in academic writing

Abstract: Academic publishing plays a visible role in the lives of academics in the contemporary university. This paper, located in the academic literacies field of critical enquiry, illustrates the complex ways in which two South African academics understood and discursively constructed their identities through their writing for a recently published book exploring lecturers’ teaching and learning contexts and practices. The autoethnographic sensitivity of the research enabled the elicitation of critical self-reflective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…A similar suggestion, to ask SoTL authors about their reading, writing, and citation strategies, was made by Cappello and Miller-Young (2020). Coleman and Morris (2021) provide a fascinating account of how they, as two South African academics, understood and discursively constructed their identities through writing about SoTL using an academic literacies framework; while Thomson (2018b) gives a brief account of her experience of undertaking a rapid evidence review. Some fascinating quotes about the messy, iterative, and cumulative process that bachelor students experienced in undertaking business research theses, may be found in the article by Juntunen and Lehenkari (2021).…”
Section: Implications For the Further Development Of An Academic Lite...mentioning
confidence: 99%
See 1 more Smart Citation
“…A similar suggestion, to ask SoTL authors about their reading, writing, and citation strategies, was made by Cappello and Miller-Young (2020). Coleman and Morris (2021) provide a fascinating account of how they, as two South African academics, understood and discursively constructed their identities through writing about SoTL using an academic literacies framework; while Thomson (2018b) gives a brief account of her experience of undertaking a rapid evidence review. Some fascinating quotes about the messy, iterative, and cumulative process that bachelor students experienced in undertaking business research theses, may be found in the article by Juntunen and Lehenkari (2021).…”
Section: Implications For the Further Development Of An Academic Lite...mentioning
confidence: 99%
“…Academic identity is a core feature of the academic literacy literature (e.g., Coleman and Morris 2021;Lea and Stierer 2009;. The concept of identity helps to understand the different ways that academics see the process of undertaking a literature review.…”
mentioning
confidence: 99%
“…Gourlay (2009) suggests that academic literacies are "threshold practices" which can lead to a reinforced sense of identity as a student. This idea may also be applied to the transition process that those new to SoTL go through as they develop their SoTL identities through reading, writing, searching, and reviewing SoTL (Coleman and Morris 2021).…”
Section: An Academic Literacies Perspective On Searching the Sotl Lit...mentioning
confidence: 99%